Sweden : 2011 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sweden. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, economic developments and policies used for the recovery of financial stability of Sweden against global recession are discussed. The low inflation is reached by increasing Riksbank policy rate. The role of fiscal policy council is explained. The Financial Sector Assessment Program (FSAP) recommendations are endorsed on financial institutions. These include merging the stability and deposit insurance funds, establishing a special bank resolution regime, and increasing further the Financial Supervisory Agency's capacity. Also, the Basel III capital regulations are supported by the authorities.